Glycosylated Hemoglobin Testing in the National Social Life, Health, and Aging Project - Gregg, Forest T. (J Gerontol B Psychol Sci Soc Sci, 2014)
OBJECTIVES. Longitudinal biomeasures of health are still new in nationally representative social science survey research. Data measuring blood sugar control provide opportunities for understanding the development of diabetes and its complications in older adults, but researchers must be aware that some of the differences across time can be due to variations in measurement procedures. This is a well-recognized issue whenever all samples cannot be assayed at the same time and we sought to present the analytic methods to quantify and adjust for the variation. METHOD. We collected and analyzed HbA1C, glycated hemoglobin, a biomeasure of average blood sugar concentrations within the past few months. Improvements were made in the collection protocol for Wave 2, and assays were performed by a different lab. RESULTS. The HbA1C data obtained during Wave 1 and Wave 2 are consistent with the expected population distributions for differences by gender, age, race/ethnicity, and diabetes status. Age-adjusted mean HbA1C declined slightly from Wave 1 to Wave 2 by −0.19 (95% confidence interval [CI]: −0.27, −0.10), and the average longitudinal change was −0.12 (95% CI: −0.18, −0.06). DISCUSSION. Collection of HbA1C in Wave 2 permits researchers to examine the relationship between HbA1C and new health and social measures added in Wave 2, and to identify factors related to the change in HbA1C. Changes in collection protocol and labs between waves may have yielded small systematic differences that require analysts to carefully interpret absolute HbA1C values. We recommend analytic methods for cross wave differences in HbA1C and steps to ensure cross wave comparability in future studies